Implementation of Hydroponics and Fish Cultivation in The Bucket (BUDIKEMBER) for Detecting Insect Biodiversity in Medan City, North Sumatra - Siregar, Ameilia Zuliyanti; Tulus; Zulkifli Nasution; Nismah Panjaitan (UPT Publikasi Ilmiah UNISBA, 2025)
The community service activity was carried out by the community service team under the International Cooperation Service Scheme of the Community Service Research Institute (LPPM) of the University of Sumatera Utara (USU) by inviting the Pujakesuma community, family welfare empowerment, and the community at Griya Nusa Tiga, aiming to introduce and implement hydroponic and fish cultivation in the bucket (Budikdamber) techniques to participants through lectures and practical training sessions. The community services were conducted from August to September 2024, involving 40 respondents from Griya Nusa Tiga Complex, Medan, North Sumatra. Research data was obtained through field observations, data collection, and interviews. The hydroponic systems applied to mustard greens and kale demonstrated advantages in terms of shorter harvest times and efficient yields; meanwhile, cultivating catfish in a bucket with the benefit of kale insects in the system improved plant quality and productivity, reduced pesticide use, and lowered production costs. The training also included hands-on practice, nutrient and water management, and result evaluation, allowing 40 participants to analyze challenges and solutions. Overall, the activity contributed to environmental sustainability, supporting community development through more efficient and eco-friendly practices with significant economic and ecological benefits.